Redeeming class under the lens of historical materialism - Victor Pastore (Revista Mundos do Trabalho, 2020)
Book review: MATTOS, Marcelo Badaró. A classe trabalhadora: de Marx ao nosso tempo. São Paulo: Boitempo, 2019.